Synthesis, Structural and Biological Studies of Chromium(III) ,Manganese(II),Cobalt(II),Nickel(II),Copper(II) and Zinc(II) Complexes with Tere Dentate N2O Donor Azo-based Coumarin Ligand - MAHMOOD NAJM ALOTHMAN; HIBA YOUSIF ALAZAWI (Journal of Global Pharma Technology, 2018)
The present work describes the synthesis and characterization and biological studies of new transition metal complexes derived from Azo ligand(LH) of 6-hydroxycoumarine. The new azo LH was synthesized from condensation the diazonum salt chloride of 5-methylmercapto-2-amino-1,3,4-thiadiazole with alkaline solution of 6-hydroxycoumari at 0 C temperature. The octahedral geometry was adopted fpr the prepared complexes in 2:1 mole ratio of L/M up on CHNM analyses and other spectroscopic methods. The ligand LH and metal complexes were confirmed their structures with the help of CHNM analyses, NMR, MS, UV-Visibel spectra and magnetic and molar conductivity measurements. The biological assays of the solutions of LH and it s metal complexes in DMSO solvent were screenec against some positive, negative grams bacteria and some fungal organisms. The observed results from diffusion method revealed that almost metal complexes have higher activity rather than the free solutions ofv LH due to the chelation theory of inhibition zone